Projected climate change impacts on streamflow in the Upper Oum Er Rbia Basin, Upstream of the Ahmed El Hansali Dam, Morocco - Tarik El Orfi; Mohamed El Ghachi; Sébastien Lebaut; Ionel Haidu (Environmental Challenges)
Climate change is reshaping water resource availability, with serious implications for regions dependent on stable dam supplies. This study explores the projected impacts of climate change on streamflow in Morocco's Upper Oum Er Rbia Basin, specifically assessing the implications for water supply to the Ahmed El Hansali Dam. Using the SWAT model, driven by climate data on precipitation and temperature sourced from five regional models in the Euro-CORDEX initiative under scenarios RCP 4.5 and RCP 8.5, future runoff was simulated across three critical timeframes: the near future (2025–2050), mid-century (2051–2075), and late century (2076–2100), with comparisons made to a historical baseline (1981–2010). Results reveal significant potential changes, with projections indicating declines in precipitation by 21% to 45% and temperature increases of 24% to 43% by 2100. These shifts are expected to reduce average river flows by 23% to 53%. Specifically, flow rates are projected to decline by 10–20% for the Oum Er Rbia, 25–48% for the Srou, and 38–49% for the Ouaoumana rivers, all vital contributors to the dam's reservoir. Consequently, the dam's annual water supply, historically around 720 hm³, could decrease by 118 to 288 hm³. Winter, the most crucial season for water supply to the dam, is expected to be particularly impacted, with flow reductions of 22–51%, equating to losses of 60 to 139 hm³. These findings underscore the need for adaptive water management strategies and highlight the urgency for climate-resilient planning measures, offering critical insights to support decision-makers in safeguarding water resources under changing climatic conditions.